2011
DOI: 10.1111/j.1755-6686.2011.00232.x
|View full text |Cite
|
Sign up to set email alerts
|

How Do Thai Patients With End Stage Renal Disease Adapt to Being Dependent on Haemodialysis? A Pilot Study

Abstract: Thai patients with ESRD felt treatment, including HD, adversely affected their lives and required physical, psychological and social changes to enable them to cope. They reported use of a range of strategies to deal with the adverse effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 15 publications
0
14
0
2
Order By: Relevance
“…Ko et al, 2007;Martinez and Custodio, 2014) and studying a non-representative sample of the dialysis population such as African Americans (Spinale et al, 2008;Thomas and Washington, 2011) or women only (Tanyi and Werner, 2008b). One qualitative study in this review (Yodchai et al, 2011) recruited a sample of only five participants and so, based on its findings, it might not be possible to conclude that all patients employ spirituality/religion as a way of coping with their disease.…”
Section: Sample Size and Studied Populationmentioning
confidence: 99%
See 4 more Smart Citations
“…Ko et al, 2007;Martinez and Custodio, 2014) and studying a non-representative sample of the dialysis population such as African Americans (Spinale et al, 2008;Thomas and Washington, 2011) or women only (Tanyi and Werner, 2008b). One qualitative study in this review (Yodchai et al, 2011) recruited a sample of only five participants and so, based on its findings, it might not be possible to conclude that all patients employ spirituality/religion as a way of coping with their disease.…”
Section: Sample Size and Studied Populationmentioning
confidence: 99%
“…They found that spirituality is essential in buffering against and reducing anger, depression, anxiety, and bitterness, and thereby fosters coping. Correspondingly, in Thailand, patients also reported that spirituality helps them to adapt to HD treatment and to maintain role function and interdependence as well as coping with the mental challenges of HD (Yodchai et al, 2011).…”
Section: Spirituality In the Lives Of Patients With End-stage Renal Dmentioning
confidence: 99%
See 3 more Smart Citations